Severe ileum bleeding following adjuvant capecitabine chemotherapy for locally advanced colon cancer: a case report and review of the literature - You Zou (BMC, 2021)
Abstract Background Capecitabine is a prodrug that is enzymatically converted to its active form, fluorouracil (also called 5-fluorouracil), which is commonly used as adjuvant chemotherapy in colorectal cancer patients. Severe gastrointestinal bleeding induced by capecitabine is rare. Here, we are presenting the first case report of surgery specimen assisted diagnosis of this uncommon condition. Case presentation A 63-year-old Chinese male with a history of colon adenocarcinoma and right hemicolectomy presented with severe lower gastrointestinal bleeding 2 days after finishing capecitabine administration during the first cycle of XELOX adjuvant chemotherapy. Because of the negative findings of active bleeding points by digital subtraction angiography (DSA) or colonoscopy, emergency laparotomy and partial enterectomy were performed. The bloody diarrhea had resolved after surgery and a terminal ileitis was diagnosed after pathological examination of the surgical specimen. Conclusions Terminal ileitis induced by capecitabine is likely to be underreported. It should be considered more often as a cause of severe gastrointestinal bleeding during or after treatment with capecitabine agents. Emergency surgery may achieve satisfactory outcomes if endoscopic hemostasis is ineffective. Highlights of this case 1. Gastrointestinal bleeding following capecitabine treatment in colorectal cancer patients might be life-threatening. 2. Terminal ileitis induced by capecitabine should always be considered in the differential diagnosis of severe gastrointestinal bleeding. 3. Awareness of the risk factors such as deficiency of dihydropyrimidine dehydrogenase, advanced age, or right colectomy may aid in reducing capecitabine-related morbidity. 4. When severe bleeding occurs, emergency surgery may achieve satisfactory outcomes if medical and endoscopic interventions are ineffective.